A new Aspidogyne (Orchidaceae: Goodyerinae) from the Brazilian Atlantic Forest - Smidt, Eric De Camargo; Engels, Mathias Erich; Miranda, Marcelo Rodrigues (Phytotaxa, 2016)
A new species of Aspidogyne from the Atlantic Forest in Caraguatatuba, on the northern coast of São Paulo State, Brazil, is proposed, described, illustrated and compared with closely related species. A key to the sympatric species of Goodyerinae is also provided. Aspidogyne caraguatatubensis is easily recognized by its small size, lip shape and the absence of rostellum. Among congeners, the new species resembles A. argentea, which differs by its larger size, flower color, lip with truncated apex and developed rostellum.